A CONCEPTUAL STUDY OF RAKTAVAHA SROTAS AND ITS DISEASE - Rongson, *Sangeeta; Barman, Niten (International Journal of Ayurveda and Pharma Research, 2017)
Srotas is the channel that transports only Dhatu under metabolic transformation. Some authors views that Srotas can be interpreted as micro- vascular carrier, which specialized for exchange of the materials. The exchange of materials between interstial fluid and intra capillary substance move through highly specific pores which are called Ayana. Number of Srotas are different by different authors. The Srotas have their own Mulasthan or root. Chakrapani mentioned Moolasthana of Srotas as Prabhavasthana means the anatomical seat of respective Srotas, main seat of pathological changes, having diagnostic value or its be the focus of treatment. Raktavahasrotas is the Srotas which carry Rakta (blood). Its Mulasthana is given Yakrit, Pleeha and Raktavahinidhamani mentioned the Ayurvedic samhita. Due to intake of the Vidahianna and Pana, Snigdhaaahar, Ushnadrava along with exposure to sunlight and air leads to Raktavahasrotasdusti. Sushruta said if there is cut or piercing injury to Mulasthana of Raktavahisrotas, it causes cyanosis in the body parts, fever, burning sensation, pallor, hemorrhage and blood – shot eyes. The disease of the Raktavahasrotas are Kustha, Visrpa, Pidika, Kamala, Asrgdar, Arubuda, Arsa etc. all the skin diseases, hemolytic disease, gynecological disorders, metabolic disorders come under Raktavahasrotas. The treatment principle is bloodletting, purgation and fasting. Therefore Raktavahasrotas is related to haemopoetic system and circulatory system from its root system liver and spleen. The diseases of Raktavahasrotas is important to the point of diagnosis and clinical practices.